The Future of Education: Integrating Technology with Interactive Teaching Methods - Ilyas Ilyas; Muchsin Muchsin (PT. Anagata Sembagi Education, 2025)
The integration of digital technology in education has brought significant changes, especially through the implementation of Learning Management System (LMS), artificial intelligence (AI), and augmented reality (AR). LMS allows flexibility in learning, while AI helps in personalization of materials and identification of students' learning difficulties. AR, on the other hand, enriches the learning experience with interactive visualizations. In addition, game-based learning approaches and virtual reality (VR) technology enhance students' motivation and understanding of complex material. However, the application of this technology still faces challenges, such as limited infrastructure in remote areas, educator readiness, and digital access gaps. This study used descriptive qualitative methods with interviews, observations and document analysis of 30 respondents consisting of teachers, students and educational technology developers. The results show that technology integration improves student engagement and learning effectiveness, but still requires infrastructure support and training for educators. To optimize the implementation of technology in education, synergy is needed between the government, educational institutions and the private sector in providing adequate facilities and training. With the right strategy, technology can be a catalyst in creating a more adaptive, inclusive and up-to-date education system.